A search for an excited muon decaying to a muon and two jets in pp collisions at √ s = 8 TeV with the ATLAS detector - Santos, S. P. Amor dos (2016)
Anew search signature for excited leptons is explored. Excited muons are sought in the channel pp → μμ∗→ μμ jet jet, assuming both the production and decay occur via a contact interaction. The analysis is based on 20.3 fb-1 of pp collision data at a centre-of-mass energy of s = 8 TeV taken with the ATLAS detector at the large hadron collider. No evidence of excited muons is found, and limits are set at the 95% confidence level on the cross section times branching ratio as a function of the excited-muonmass μμ∗. For μμ∗between 1.3 and 3.0 TeV, the upper limit on φB (μ∗→ μqq) is between 0.6 and 1 fb. Limits on sB are converted to lower bounds on the compositeness scale. In the limiting case L = μμ∗, excitedmuonswith amass below2.8 TeVare excluded.With the samemodel assumptions, these limits at larger μ∗masses improve upon previous limits fromtraditional searches based on the gauge-mediated decay μ∗→ μγ.